Definitions of male homosexuals in school dictionaries - Santos, Hugo Leonardo Gomes dos (2021)
With the development of linguistic theories and Lexicography itself, several different researches and approaches were proposed to account for the production and reception of lexicographic definitions. In this research, based on the discussions about definition in the scope of Metalexicography (BOLINGER, [1985] 2008; BUGUEÑO MIRANDA, 2009; PONTES, 2009; PORTO DAPENA, 2002; WELKER, 2004), we investigate the linguistic resources used in the type 3 school dictionaries to mean male homosexuals. Based on data from Santos (2016), we analyze the entry words ‘gay’, ‘homossexual’, ‘maricas’ and ‘pederasta’ from the five selected dictionaries, totaling a sample of twenty entries. The definitions were analyzed according to the definition categories proposed by Porto Dapena (2002) and the results have the following distribution: 16 relational definitions (44.5%), 12 hyperonymic definitions (33.3%), 6 synonymic definitions (16.7%) and 2 pseudoperipheral definitions (5.5%). It was found in the sample a trend to use relational definitions, highlighting the metalinguistic character of the dictionaries. Another relevant aspect concerns the semantic features used in the definitions that bring up discussions about social gender and sexuality.